Acute Effects of Ammonia Inhalants on Strength and Power Performance in Trained Men. Issue 1 (January 2018) - Bartolomei, Sandro; Nigro, Federico; Gubellini, Luca; Semprini, Gabriele; Ciacci, Simone; Hoffman, Jay R.; Merni, Franco
Abstract : Abstract: Bartolomei, S, Nigro, F, Luca, G, Gabriele, S, Ciacci, S, Hoffman, JR, and Merni, F. Acute effects of ammonia inhalants on strength and power performance in trained men. J Strength Cond Res 32(1): 244–247, 2018—The aim of the present study was to investigate the influence of ammonia inhalants on lower body power and maximal isometric strength in trained men. Twenty experienced resistance trained men (age = 26.7 ± 3.7 years; body weight = 80.59 ± 9.0 kg; body height = 179.5 ± 5.7 cm) were tested for counter movement jump power (CMJP), maximal force, and peak rate of force development (pRFD20) expressed during an isometric midthigh pull (IMTP). Assessments were performed using either an ammonia inhalant (AI), a placebo (PL), or no inhalants (N). One-way analysis of variance (ANOVA) with repeated measures was used to compare strength and power performance between the different trials. A significant ( p < 0.01) increase in pRFD20 was detected following the use of AI. No significant effects of trial were noted for CMJP and IMTP maximal force ( p = 0.251 and p = 0.075, respectively). Results of the present study showed a potential ergogenic effect of AI on rate of force development (i.e., explosive force output), with a trend toward an improvement in maximal force production. The mechanism of action may be related to the stimulatory action of AI often reported by athletes as a "psyching-up" effect. The positive effect of AI on the rate of force development may represent an advantage in sports requiring high rates of force production.